Peers and teachers as the best source of social support for school engagement for both advantaged and priority education area students - Martinot, Delphine; Sicard, Alyson; Gul, Birsen; Yakimova, Sonya; Taillandier-Schmitt, Anne; Maintenant, Célia (Frontiers in Psychology, 2022)
Promoting student school engagement is a major goal in our society. The literature has shown that students' proximal sources of social support can play a fundamental role in facilitating this engagement. The purpose of this study was (1) to compare perceived support from four sources (mother, father, teacher, peers) as a function of two different middle-school student backgrounds, a priority education area and a privileged area; (2) and (3) to examine the contribution of these main sources of social support, either directly or indirectly (through sense of school belonging) to school engagement; and (4) to test whether perceived social support is more strongly related to school engagement, directly or indirectly, among students from priority education school compared to students from advantaged area. In all, 623 middle-school students (aged 11 to 16) from either a privileged or priority education area participated to this study. The results showed that the mother was perceived as providing more support, followed by the father, the teachers and the peers. Students from the priority education area perceived more support from their teachers than their counterparts from the more privileged area did. A path analysis showed that each source of social support, except for maternal support, contributed to school engagement. Peers and teachers emerged as the best source of support for school engagement, having significant direct effects among students from priority education area and both direct and indirect (through the sense of school belonging) effects among students from advantaged area. Peer support also appears to have a double-edged effect for school engagement among students in the priority education area. This study contributes to enlightening the phenomenon of school engagement in adolescence by clarifying the role of social support and related mediating process. Being perceived as an important source of social support by students is not enough to contribute to their sense of school belonging and school engagement.